Regional Cooperation and Resilience in East Asia - Sebastian Bobowski (Routledge, 2024)
This book argues that a resilient region should act reactively and proactively in the face of shocks and disruptions and asserts that the institutionalization of regional cooperation may be the answer to development challenges in times of uncertainty and instability. It considers regional, transregional, and subregional cooperation initiatives for building regional resilience and critically examines a broad spectrum of issues, such as international security and trade, economic development, value chains in production, and social welfare. Adopting the concept of resilience allows for a holistic, dynamic, and systematic approach to the studies on the regional process of institutionalization, responsiveness, and adaptability to challenging circumstances. The economic and social indicators of the countries in the region are examined alongside an analysis of the regional institutional architecture. The reader is acquainted with the essence of resilience concerning each category of challenges and the mechanisms of its achievement and strengthening through regional integration. The interdisciplinary character of the book makes it suitable for usage not only by economists but also by lawyers. As such, the book will be helpful to scholars and students of international economics, international security, and policymakers.
Keywords: 320; East Asia; economic value chain and social resilience; security; regional resilience; regional integration